2016
DOI: 10.3133/sir20165081
|View full text |Cite
|
Sign up to set email alerts
|

Methods for estimating annual exceedance probability discharges for streams in Arkansas, based on data through water year 2013

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit http://store.usgs.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The decision was made based on comparative studies in Australia (Haddad et al, ; Haddad & Rahman, ; Haddad, Rahman, & Ling, ). In the United States, the U.S. Geological Survey (USGS) has recently conducted regional skew studies in several states employing the Bayesian GLS framework suggested in Reis et al () and further developed in Gruber et al () (Eash et al, ; Feaster et al, ; Gotvald et al, ; Gotvald et al, ; Lamontagne et al, ; Mastin et al, ; Olson, ; Over et al, ; Parrett et al, ; Paretti et al, ; Southard & Veilleux, ; Weaver et al, ; Wagner et al, ; Wood et al, ; Zarriello, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision was made based on comparative studies in Australia (Haddad et al, ; Haddad & Rahman, ; Haddad, Rahman, & Ling, ). In the United States, the U.S. Geological Survey (USGS) has recently conducted regional skew studies in several states employing the Bayesian GLS framework suggested in Reis et al () and further developed in Gruber et al () (Eash et al, ; Feaster et al, ; Gotvald et al, ; Gotvald et al, ; Lamontagne et al, ; Mastin et al, ; Olson, ; Over et al, ; Parrett et al, ; Paretti et al, ; Southard & Veilleux, ; Weaver et al, ; Wagner et al, ; Wood et al, ; Zarriello, ).…”
Section: Introductionmentioning
confidence: 99%
“…The decision was made based on comparative studies in Australia Haddad, Rahman, & Ling, 2015). In the United States, the U.S. Geological Survey (USGS) has recently conducted regional skew studies in several states employing the Bayesian GLS framework suggested in and further developed in Gruber et al ( 2007) (Eash et al, 2013;Feaster et al, 2009;Gotvald et al, 2009;Gotvald et al, 2012;Lamontagne et al, 2012;Mastin et al, 2016;Olson, 2014;Over et al, 2016;Parrett et al, 2011;Paretti et al, 2014;Southard & Veilleux, 2014;Weaver et al, 2009;Wagner et al, 2016;Wood et al, 2016;Zarriello, 2017). This paper starts with the Bayesian GLS model error variance estimator in and develops a complete analysis framework including a range of new regression diagnostic statistics for both B-WLS and B-GLS analyses.…”
Section: Introductionmentioning
confidence: 99%